Characterization of Starch Edible Films with Different Essential Oils Addition - Šuput Danijela; Lazić Vera; Pezo Lato; Markov Siniša; Vaštag Žužana; Popović Ljiljana; Radulović Aleksandra; Ostojić Sanja; Zlatanović Snežana; Popović Senka (Polish Journal of Food and Nutrition Sciences)
This study investigated properties of starch-based edible films with oregano and black cumin essential oil addition. Essential oils addition positively affected film swelling (decreased due to essential oil addition), mechanical properties (tensile strength decreased while elongation at break increased), and water vapor barrier properties (decreased along with essential oils addition). Control film did not have any biological activity, which proves the need for essential oils addition in order to obtain active packaging. Oregano oil was more effective in terms of biological activity. Endothermal peak, above 200°C, represents total thermal degradation of edible films. Diffraction pattern of control film showed significant destruction of A-type crystal structure. Addition of essential oils resulted in peak shape change: diffraction peaks became narrower. Principal Component Analysis has been used to assess the effect of essential oils addition on final starch-based edible films characteristics with the aim to reveal directions for the film characteristics improvement, since the next phase will be optimal film application for food packaging.